1987
DOI: 10.1002/macp.1987.021880523
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization, melting and morphology of poly(hexamethylene sulfide)

Abstract: Poly(hexamethy1ene sulfide) fractions, ranging in molecular weight from 4600 to 20000, were isothermally crystallized from the melt state in the temperature range 50-70°C. The dependence of the melting temperature on the crystallization temperature was analyzed in experiments involving low and high levels of crystallinity. The equilibrium melting temperature corresponds to 366 K and the enthalpy of fusion was found to be 40,5 cal/g ( = 170 J/g). The isothermal overall crystallization rates were analyzed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The average undercooling predicted with eq 39 and 40 at the regime I -* II transition is thus µ = 16.22 ± 0.17 °C, which is to be compared to the experimental value _ = 16.46 ± 0.39 °C exhibited in Table I. It may be concluded that eq 39 and 40 provide an accurate and meaningful representation of the growth rate data inasmuch as they reproduce the absolute growth rates in both regimes I and II as a function of molecular weight and temperature within experimental error and at the same time yield the correct mean undercooling at the regime I -*-II transition.…”
Section: Analysis Of Growth Rate Experiments Tomentioning
confidence: 49%
See 2 more Smart Citations
“…The average undercooling predicted with eq 39 and 40 at the regime I -* II transition is thus µ = 16.22 ± 0.17 °C, which is to be compared to the experimental value _ = 16.46 ± 0.39 °C exhibited in Table I. It may be concluded that eq 39 and 40 provide an accurate and meaningful representation of the growth rate data inasmuch as they reproduce the absolute growth rates in both regimes I and II as a function of molecular weight and temperature within experimental error and at the same time yield the correct mean undercooling at the regime I -*-II transition.…”
Section: Analysis Of Growth Rate Experiments Tomentioning
confidence: 49%
“…( 71)ß-5736/ 7'ß-°.955 1 5/7,( 77The nature of the determination of s from eq 28 and 29 is shown schematically in Figure 3. Selecting a fixed AT, f (40) say 14.96 °C in regime I, which is exactly 1.5 °C above -. = 16.46 °C, one then plots log G¡ vs log nz for the 11 specimens.…”
Section: Analysis Of Growth Rate Experiments Tomentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most used extrapolation methods52–57 for the determination of the T m in conditions of thermodynamic equilibrium is based on the implicit relationship between the crystal size and the T m proposed by Gibbs58 and Thomson:59 where T italicm0 is the equilibrium melting temperature, σ ec is the interfacial free energy associated with the basal face of the crystallite and ξ is the crystal size. In this expression, it is assumed that the lateral dimensions of the lamellar crystallite are much greater than its thickness and do not depend on the nature of the interfacial structure 60.…”
Section: Resultsmentioning
confidence: 99%
“…If the family of crystals that gave rise to T m I were formed exclusively due to crystalline segregation during the isothermal crystallization process, the crystallites formed from the recrystallization phenomenon after the melting of the family associated with T m II would give rise to a third melting peak, above that of T m I because they would have been developed at a higher T c . One of the most used extrapolation methods [52][53][54][55][56][57] for the determination of the T m in conditions of thermodynamic equilibrium is based on the implicit relationship between the crystal size and the T m proposed by Gibbs 58 and Thomson: 59…”
Section: Melting Behavior After Isothermal Crystallizationmentioning
confidence: 99%